Evaluating the effectiveness of digitizing tax services to improve tax and financial oversight: A case study of the Souk Ahras Tax Center - Boughalem, Zineb; Atamnia, Amina (The International tax journal, 2025)
This study attempts to evaluate the performance of digitalizing tax services in bolstering tax and financial oversight with a special focus on Souk Ahras Province's Tax Center in Algeria. The study content analysis and organized interviews to examine the digital information system utilized within the center and workflow systems. It attempts to look at how the instruments bolster oversight performance and taxation compliance. The findings indicate that the tax department has come a long way in a bid to digitalize services offered to taxpayers and citizens in general. Particularly, the department has been integrated with a proper digital platform—SAP—to monitor and track the fiscal status of taxpayers. Tax and fiscal monitoring at the Souk Ahras Tax Center, on the other hand, still employs traditional methods, such as document verification and on-site visits. This begs for more digitization of monitoring activities in the near future.